Market structure, productivity and profitability performance of Malaysian general insurers - Mansur, Mustazar (2015)
The insurance industry in Malaysia has been increasingly competitive, especially following the economic crisis and financial liberalization process. In fact, most of the firms in the general insurance industry had suffered losses annually. Government intervention, through BNM, by introducing changes in policies and regulations, such as requirements on company solvency level, were targeted at increasing the confidence level among the insurance holders in the country. However, a large number of renowned insurance companies have taken action for sale or foreclosure due to financial difficulties or indebtedness of their companies. It is important that each company realizes that a high market share does not guarantee financial security or good performance. This paper empirically examines the relationship between market structure, productivity levels and profit performance of general insurance companies in Malaysia. In the analysis part of this study, a two structure model,represented by three main functions, that is, market share function, profitability function and productivity function, is used. This model is based on the theory of industrial organization (IO), formally known as Structure, Conduct and Performance (SCP) theory. Panel data for the 40 year period is used for determining the model estimation on market structure, productivity and profitability of general insurance firms, using Two Stage Least Square (2SLS) method. There are three main hypotheses, namely the SCP hypothesis, the Relative Market Power (RMP) hypothesis, and the Efficient-Structure (ES) hypothesis, were tested. The findings in model 1 show that general insurance firms’ profit function has a positive and significant correlation with insurers’ premium income and returns on investment. As for the profit function of the firm, it has a negative and significant relationship with market share, turnover of total assets and insurance prices. Market share has a positive and significant relationship with the level of productivity of the firm's management, market concentration ratio for the 10 largest firms and merger and acquisition activity. Conversely, other variables, such as labor productivity, returns on investment, price levels and deregulation have significant negative relationship. In terms of the productivity functions in model 2, there is a significant positive relationship between market share, productivity management, return on assets, agents’ commission and fixed assets turnover with the general insurance firms’ productivity functions. While the variable labor productivity and return on investment have significant negative correlation with the productivity of general insurance firm. The results of this study are in acceptance of SCP hypothesis on the role of market concentration ratio and market share of firms. In addition, the findings also support the ES hypothesis on the importance of management productivity and investment efficiency of firms. Past emphasis has focused on policy implications on firms and consumers, but the policy implications of BNM’s role are also important. Since BNM has assumed the regulation of the Malaysian insurance market since 1988, it has introduced several initiatives to ensure the smooth and efficient running of the insurance market. However, technological advances also important to bring the financial performance of general insurance firms better.